Tuberkulosis Paru pada Tenaga Kesehatan dengan Komorbid Hipertensi - Julyanti Chistine; Wirya Sastra Aman; Alex Setiawan (Universitas Widya Nusantara, 2025)
Pulmonary tuberculosis (TB) remains a major global health problem, particularly in high-burden countries such as Indonesia, where healthcare workers are at increased risk of infection due to repeated exposure to Mycobacterium tuberculosis in healthcare facilities. Comorbidities such as hypertension may exacerbate disease progression, reduce treatment response, and increase the risk of complications, thus requiring an integrated management approach. This case report describes a 45-year-old female healthcare worker presenting with chronic cough lasting more than one month, fatigue, weight loss, and night sweats. Diagnostic evaluations included sputum smear microscopy, GeneXpert MTB/RIF, chest radiography, and routine laboratory tests. Results showed positive sputum smear (++), rifampicin-sensitive M. tuberculosis, and infiltrates in the upper lobes of both lungs, confirming active pulmonary TB with hypertension as a comorbidity. The patient was treated with the first-line TB regimen 2HRZE/4HR based on the Directly Observed Treatment, Short-course (DOTS) strategy, along with antihypertensive therapy of amlodipine 5 mg/day. After two months of treatment, significant clinical improvement was observed, with negative sputum results and well-controlled blood pressure. Regular follow-up demonstrated high treatment adherence and progressive improvement in supportive examinations. This case highlights the importance of routine TB screening among healthcare workers, optimal management of comorbidities, and consistent application of DOTS to improve treatment success, prevent complications, and reduce the risk of nosocomial transmission. A comprehensive approach is essential to protect healthcare workers and maintain the quality of healthcare services.